Assessment of groundwater vulnerability within the cross-border areas of Ukraine and Poland - Medvid, Halyna; Yanush, Luibov; Solovey, Tatiana; Panov, Dmytro; Harasymchuk, Vasyl (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Problem statement. The growing global trend of groundwater consumption and excessive groundwater abstraction in many parts of the world requires an accurate and comprehensive assessment of the potential for groundwater resource development. The EU-WATERRES international project has begun developing a concept for coordinated management and harmonized monitoring of groundwater resources in the transboundary areas of Ukraine and Poland. Studying groundwater’s natural protection status or vulnerability is a priority, as groundwater pollution has become a significant environmental problem in recent decades due to the growth of industrial production and agricultural activities. Study objective is to analyze the existing materials on the natural protection of groundwater within the study area and to quantify the vulnerability of the main useful aquifer (MUA) to surface pollution in the cross-border Polish-Ukrainian area. Methodology involves the quantitative method of groundwater vulnerability assessment by calculating the time of pollutant penetration into the aquifer through the aeration zone using the modified Bindemann formula and GIS. Research results. Studies have shown that the most vulnerable among MUA there is an unconfined alluvial Quaternary horizon (alQ) of the Syan and Dniester River basins. Throughout its entire development, its vulnerability corresponds to the "very high" category because of pollution from the surface caused by precipitation filtration. The Upper Cretaceous aquifer (K2) is less vulnerable. The groundwater of this horizon in the Polish part of the cross-border area is more vulnerable - here the vulnerability corresponds to the categories "very high" and "high". In the Ukrainian part, the Upper Cretaceous aquifer is characterized by better natural hydrogeological conditions and is less vulnerable to pollution. The Lower Neogene aquifer, which has a limited distribution on the slopes of the Western Bug-Syan River watershed within Roztochia, is the least vulnerable to pollution as compared to the others. The lithological composition of the aeration zone and the thickness of weakly permeable and practically impermeable rocks have a decisive impact on the filtration time and vulnerability of groundwater to pollutants from the surface by infiltration. Scientific novelty of the research. For the first time, a quantitative assessment of the vulnerability of the MUAs for the Polish-Ukrainian cross-border area was carried out. The use of the results of this assessment will facilitate the adoption of appropriate management decisions for the comprehensive protection of transboundary groundwater, prevention of its pollution, and reduction of anthropogenic impact.